2012
DOI: 10.1590/s0034-737x2012000200011
|View full text |Cite
|
Sign up to set email alerts
|

Diversidade genética entre cultivares de mangueiras, baseada em caracteres de qualidade dos frutos

Abstract: Genetic diversity among cultivars of mango based on fruit quality traitsThe mango crop is one of the most significant agribusiness in Brazil. Although there are many cultivars, cultivation has been done primarily with 'Tommy Atkins' and there are few studies on characterization and analysis of genetic diversity in different areas of production. Therefore, the objective of this work was to study the genetic diversity of fifteen mango cultivars, eight from Brazil and seven from Florida (USA), produced in the Zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
(14 reference statements)
0
9
1
1
Order By: Relevance
“…Results observed for the mango were lower than those discussed by Silva et al (2012), who when studying 15 cultivars, found levels ranging from 0.2 to 3.4 g 100 g -1 in Haden and Tommy Atkins respectively. In the present study, the greatest starch content in ripe mangoes was seen in fruits of the Espada cultivar, equivalent to 0.4 g 100 g-1 (Table 5).…”
Section: Resultscontrasting
confidence: 76%
“…Results observed for the mango were lower than those discussed by Silva et al (2012), who when studying 15 cultivars, found levels ranging from 0.2 to 3.4 g 100 g -1 in Haden and Tommy Atkins respectively. In the present study, the greatest starch content in ripe mangoes was seen in fruits of the Espada cultivar, equivalent to 0.4 g 100 g-1 (Table 5).…”
Section: Resultscontrasting
confidence: 76%
“…Similar values for the total variation were detected by the first principal component and reported for other perennial species. In mango fruit, the chemical variables were explained by PC1 (45.7%), PC2 (20.9%), and PC3 (16.9%) (SILVA et al, 2012). In palm oil (Elaeis guineensis Jacq.…”
Section: Resultsmentioning
confidence: 99%
“…Given the importance of quantitative characters for breeding programs, studies have been conducted with multivariate techniques for various species such as vine (BORGES et al, 2010;BATISTA et al, 2015), mango (SILVA et al, 2012), banana (ALVES et al, 2012), strawberry (MORALES et al;2011), papaya (RODRIGUES et al, 2010, and palm oil (OKOYE et al, 2007) trees.…”
Section: Introductionmentioning
confidence: 99%
“…Carvalho et al (2004) registered average TA values range 0.07-0.3 g citric acid 100 g -1 of pulp in mature fruits of mango cv. Palmer, whereas Silva et al (2012b) reported 0.20 g citric acid 100 g -1 of pulp also for cv. Palmer.…”
Section: Resultsmentioning
confidence: 97%